O problema de Gettier e a epistemologia do raciocínio - Fett, João Rizzio Vicente (2016)
Legend has it that up until the beginning of the latter half of the twentieth century, the philosophical community had tacitly accepted a tripartite analysis of knowledge harking back to Classical Antiquity – the Platonic Legacy. Such an epistemological perspective consists of ancient background assumptions which define 'knowledge' in terms of 'justified true belief'. In 1963, the philosopher Edmund Gettier refuted the sufficiency of this definition, showing to epistemologists that there are cases where it is possible for one to believe truly and justifiably some proposition without having knowledge of it, because the belief turns out to be true just by accident. The Gettier problem requires us to come up with a modified analysis of knowledge which withstands those counterexamples presented by Gettier. In this essay, we examine one of the attempts to solve that problem: the defeasibility theory of knowledge, proposed by Peter Klein. We furnish the reader with good reasons to believe that, unanswered objections notwithstanding, the defeasibility theory offers a promising and interesting analysis of knowledge. Recently, however, the defeasibility theory was faced with a new challenge: the problem of knowledge from falsehood. During the last decade, many purported cases of inferential knowledge based on false beliefs have been put forward in the literature, going against an entrenched Aristotelian thesis on inferential knowledge, according to which only knowledge can produce knowledge. Our last task in this essay is to show in what way Klein’s defeasibilism handles that problem and how it accommodates the possibility of there being knowledge from falsehood.